Is Individualism Suicidogenic? Findings From a Multinational Study of Young Adults From 12 Countries - Eskin, Mehmet; Tran, Ulrich S.; Carta, Mauro Giovanni; Poyrazli, Senel; Flood, Chris; Mechri, Anwar; Shaheen, Amira; Janghorbani, Mohsen; Khader, Yousef; Yoshimasu, Kouichi; Sun, Jian-Min; Kujan, Omar; et al. (Frontiers in Psychiatry, 2020)
The associations of individualistic versus collectivistic value orientations with suicidal ideation and attempts, attitudes towards suicide and towards suicidal individuals, and psychological distress were investigated across 12 nations (N = 5572 university students). We expected differential associations of value orientations with suicidal behavior and moderating effects of the prevailing value orientations in the various countries. Findings showed that intermediate levels of individualism appeared protective against suicide attempts across all investigated nations, but that, otherwise, there seemingly are no universal associations of individualism and collectivism with suicidal behaviors. High collectivism was associated with less suicidal ideation only in individualistic countries. Low individualism appeared to be a risk factor for suicidal ideation specifically in Muslim collectivistic cultures, whereas high individualism in Asian collectivistic cultures. Collectivistic values are uniformly associated with less permissive attitudes to suicide, whereas individualistic values with a more stigmatized view of suicidal behavior. Both individualistic and collectivistic values were associated with socially accepting attitudes to a suicidal peer, helping a suicidal friend, and emotional involvement. The associations of individualistic and collectivistic values with disapproving attitudes to suicidal disclosure were complex. Beliefs in punishment after death for suicide, seeing suicide as mental illness, and emotional involvement with a suicidal friend were lower in high-suicide-rate countries. These evidence patterns are discussed in the light of related research evidence, along with directions for future research in this area.